2021
DOI: 10.3390/su13137431
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Perspectives on the Role of Empathy during COVID-19’s First Wave

Abstract: The COVID-19 pandemic has spread throughout the world, and concerns about psychological, social, and economic consequences are growing rapidly. Individuals’ empathy-based reactions towards others may be an important resilience factor in the face of COVID-19. Self-report data from 15,375 participants across 23 countries were collected from May to August 2020 during the early phases of the COVID-19 pandemic. In particular, this study examined different facets of empathy—Perspective-Taking, Empathic Concern, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…), as well as our previous data ( Burkova et al, 2021 ), we conclude, that feelings of anxiety as well as being stressed is a normal reaction of the human psyche in the face of global threat. Age, sex, education, living conditions, having family, economic status, access to internet and mobile communications are among the universal factors potentially affecting personal anxiety during pandemic ( Burkova et al, 2021 ; Butovskaya et al, 2021 ; Semenova et al, 2021 ). Individuals reacted differently to a health-threatening condition such as COVID-19, based on their own illness behavior - this concept to describe the different ways in which individuals may perceive, evaluate, and react to certain physical symptoms ( Mechanic, 1995 ; Cosci and Guidi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…), as well as our previous data ( Burkova et al, 2021 ), we conclude, that feelings of anxiety as well as being stressed is a normal reaction of the human psyche in the face of global threat. Age, sex, education, living conditions, having family, economic status, access to internet and mobile communications are among the universal factors potentially affecting personal anxiety during pandemic ( Burkova et al, 2021 ; Butovskaya et al, 2021 ; Semenova et al, 2021 ). Individuals reacted differently to a health-threatening condition such as COVID-19, based on their own illness behavior - this concept to describe the different ways in which individuals may perceive, evaluate, and react to certain physical symptoms ( Mechanic, 1995 ; Cosci and Guidi, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has been a global challenge and has come to change the population’s daily life. Data using a sample of adults from different countries from 2020 to 2021 showed that social isolation, loneliness, and limitations are associated with worse mental and physical health ( Berta et al, 2020 ; Brooks et al, 2020 ; Cao C. et al, 2020 ; Chen et al, 2020 ; Kowal et al, 2020 ; Mækelæ et al, 2020 ; van Bavel et al, 2020 ; Burkova et al, 2021 ; Butovskaya et al, 2021 ; Rodríguez et al, 2021 ; etc.). The negative psychological impact of the epidemic was demonstrated on the general population, as well as on children and the elderly ( Cao C. et al, 2020 ; Chen et al, 2020 ; Fedenok and Burkova, 2020 ; Li et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of a cross-cultural study in 23 countries of the world [ 5 ] also showed a significantly higher self-image on all three scales of empathy in women compared to men. The maximum ratings on the decentration scale were obtained for the United States, Brazil, Italy, and Croatia; on the empathic concern scale during the lockdown of the first wave of the pandemic, for the United States, Brazil, Hungary, Italy, and Indonesia; and on the empathic distress scale, for Brazil, Turkey, Italy, and Indonesia.…”
Section: Empathy and Compassion Under The Pandemic In Russia: First ...mentioning
confidence: 99%